PKM EDUKASI MITIGASI BENCANA ALAM BERBASIS GEOMORFOLOGI UNTUK ANAK SEKOLAH DASAR DI SDN 101 KENDARI - La Ode Hadini; Tahir Tahir; Ahmad Hidayat; Nur Hasanah (Bajang Institute, 2025)
Kendari City is characterized by varied geomorphological conditions such as hills, alluvial plains, river valleys, and coastal areas that contribute to hydro-meteorological and geological disaster risks. However, understanding and awareness of disaster mitigation among elementary school students remain limited. This community service project aims to improve students’ knowledge of landform characteristics and their relation to disaster potential, as well as to equip them with practical mitigation skills. The program consisted of preparation, implementation, and evaluation stages, involving 22 participants from SDN 101 Kendari. Activities included focus group discussions, interactive education on geomorphological concepts, poster-making, disaster card games, and simulations of earthquakes, floods, and landslides. Results show an increase in students’ understanding and alertness, reflected in their ability to identify disaster-prone landforms and perform mitigation actions practiced during simulations. Teachers also showed increased motivation to integrate disaster education into classroom learning. This program effectively fosters disaster awareness in early education and can be developed into a sustainable school-based program.